Nicotinic Receptors: Role in Addiction and Other Disorders of the Brain - Geeta Sharma (Substance Abuse: Research and Treatment, 2008)
Nicotine, the addictive component of cigarette smoke has profound effects on the brain. Activation of its receptors by nicotine has complex consequences for network activity throughout the brain, potentially contributing to the addictive property of the drug. Nicotinic receptors have been implicated in psychiatric illnesses like schizophrenia and are also neuroprotective, potentially beneficial for neurodegenerative diseases. These effects of nicotine serve to emphasize the multifarious roles the drug, acting through multiple nicotinic acetylcholine receptor subtypes. The findings also remind us of the complexity of signaling mechanisms and stress the risks of unintended consequences of drugs designed to combat nicotine addiction.